Pengaruh Perputaran Modal Kerja, Cash Holding, Dan Ukuran Perusahaan Terhadap Profitabilitas: Studi Pada Perusahaan Sektor Teknologi Yang Terdaftar di BEI Periode 2020 – 2022 - Dahlia Fatiyana Putri; Anita Kusuma Dewi; Rusmianto Rusmianto (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Profitability is one of the key indicators of a company's financial health and performance, reflecting its ability to generate profit through effective management policies, which in this study is measured by the Net Profit Margin (NPM). This research aims to examine the impact of working capital turnover, cash holding, and firm size on profitability. The study population consists of technology sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. The sample selection was carried out using purposive sampling, yielding a sample of 10 companies that met the criteria. The hypothesis testing tool is IBM SPSS Statistics 2022 version 26, utilizing multiple linear regression analysis. The findings indicate that, partially, working capital turnover negatively affects profitability, cash holding has no effect on profitability, and firm size positively affects profitability.